Oral health-related beliefs among a sample of pregnant women in Southwestern Ontario: a descriptive study - Kamalabadi, Yasaman Mohammadi; Campbell, M. Karen; Gratton, Robert; Athanasakos, Alexia; Haddad, Myriam; Jessani, Abbas (Frontiers in Oral Health, 2024)
IntroductionUnfavorable beliefs about oral health and dental treatment during pregnancy can lead to the avoidance of dental care and the underutilization of dental services, adversely affecting adherence to good oral hygiene practices and, consequently, the health of the fetus. This study investigated the commonly held oral health beliefs among pregnant women in Southwestern Ontario, Canada.MethodsParticipants were recruited from the Family Medicine Obstetrics Clinic in London, Ontario, Canada. Eligible participants were pregnant women aged 18 or older, excluding those unwilling to participate. Participants completed a 33-item self-administered questionnaire, including three open-ended questions about oral health beliefs and their impacts on pregnancy, which were analyzed for this study. Thematic analysis in NVivo identified key patterns, while analysis determined the most common beliefs and the degree of diversity in responses. Responses were categorized into sub-themes, and the frequency and percentage of each category were calculated.ResultsA total of 130 participants met the inclusion criteria. Among them, 40.7% (n = 46) believed that oral health impacts their child's health, 48.2% (n = 53) believed that dental treatment affects fetal health, and 64.4% (n = 76) believed that pregnancy influences their oral health. Many beliefs regarding oral health during pregnancy regarded infection risks. Participants held negative beliefs about the effects of antibiotics, analgesics, and dental x-rays during pregnancy. Common beliefs about the impacts of pregnancy on oral health included developing conditions, such as tooth sensitivity, caries, and gingivitis, as well as a loss of minerals to the fetus.ConclusionThis study revealed important misconceptions and concerns about oral health and dental treatment among pregnant women in Southwestern Ontario. The findings highlighted the need for enhanced oral health education for pregnant women to address these misconceptions and promote proper care during pregnancy. Healthcare providers are encouraged to focus on dispelling myths, emphasizing the safety of necessary dental treatments, and reinforcing the significance of maintaining good oral health for maternal and fetal well-being.